2021
DOI: 10.1016/j.ymgmr.2021.100785
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative muscle ultrasound and electrical impedance myography in late onset Pompe disease: A pilot study of reliability, longitudinal change and correlation with function

Abstract: Background/objectives Late-onset Pompe disease (LOPD) is slowly progressive, making it difficult to assess clinical change and response to interventions. In this study, quantitative muscle ultrasonography (QMUS) and electrical impedance myography (EIM) were evaluated as potential biomarkers. Methods 25 patients with confirmed LOPD were recruited from the Duke Pompe Clinic and evaluated with standard clinical measures, QMUS, standard EIM (sEIM) and hand-held EIM (hEIM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
7
0
3
Order By: Relevance
“…Such information would provide additional support for the use of EIM as a non-invasive biomarker of muscle health. To this end, one very recent pilot study has correlated EIM outcomes with measures of muscle strength and function in several patients with late-onset Pompe disease 29 , suggesting that EIM could serve as a potential biomarker of clinical change and response to interventions in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Such information would provide additional support for the use of EIM as a non-invasive biomarker of muscle health. To this end, one very recent pilot study has correlated EIM outcomes with measures of muscle strength and function in several patients with late-onset Pompe disease 29 , suggesting that EIM could serve as a potential biomarker of clinical change and response to interventions in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the resistance measured in EIM is not the same as the muscle stiffness measure in elastography, although this would be better studied in disease states such as dystrophic muscle, which has a large amount of fibrotic tissue. Other studies have sought to correlate EIM with quantitative muscle ultrasound parameters but they also did not demonstrate good correlations 24,25 . Future studies comparing EIM and elastography in different neuromuscular disorders may provide further information about the two measurements of muscle physiology.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have sought to correlate EIM with quantitative muscle ultrasound parameters but they also did not demonstrate good correlations. 24,25 Future studies comparing EIM and elastography in different neuromuscular disorders may provide further information about the two measurements of muscle physiology.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the EIM and ultrasound could be applied jointly to depict muscle architecture ( Rutkove et al, 2010 ; Rutkove and Darras, 2013 ; Johnson et al, 2018 ; Hu et al, 2019 ; Longo et al, 2021 ). With the development of quantitative ultrasound, its relationship with EIM is playing an increasing important role in improving disease diagnosis ( Rutkove et al, 2014b ; Shklyar et al, 2015 ; Hobson-Webb et al, 2018 , 2021 ; Roy et al, 2019 ). Shklyar et al (2015) reported that composite data from EIM and quantitative ultrasound can better predict the muscle function compared with individual measurement data.…”
Section: Combination Of Eim and Morphological Assessmentmentioning
confidence: 99%